2001
DOI: 10.1038/sj.onc.1204529
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor protein menin interacts with NF-κB proteins and inhibits NF-κB-mediated transactivation

Abstract: Multiple endocrine neoplasia type 1 is an autosomal dominant tumor syndrome. Manifestations include neoplasms of the parathyroid glands, enteropancreatic neuroendocrine cells, and the anterior pituitary gland. The MEN1 tumor suppressor gene encodes menin, a 610 amino acid nuclear protein without sequence homology to other proteins. To elucidate menin function, we used immunoprecipitation to identify interacting proteins. The NF-kB proteins p50, p52 and p65 were found to interact speci®cally and directly with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
151
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(155 citation statements)
references
References 37 publications
(36 reference statements)
2
151
1
1
Order By: Relevance
“…Additionally, the tumor suppressor CYLD blocks NF-kB and Bcl-3 activation through its deubiquitinating activity (Kovalenko et al, 2003;Trompouki et al, 2003;Massoumi et al, 2006). Moreover, the tumor suppressor menin, which is mutated/deleted in parathyroid tumors, was reported to bind and suppress NF-kB activation (Heppner et al, 2001). Regarding the tumor suppressor p53, it was reported that p53 generally inhibits NF-kB function, and vice versa (Webster and Perkins, 1999); however, more complex relationships between p53 and NF-kB have emerged (see below).…”
Section: Inhibition Of Nf-jb By Tumor Suppressorsmentioning
confidence: 99%
“…Additionally, the tumor suppressor CYLD blocks NF-kB and Bcl-3 activation through its deubiquitinating activity (Kovalenko et al, 2003;Trompouki et al, 2003;Massoumi et al, 2006). Moreover, the tumor suppressor menin, which is mutated/deleted in parathyroid tumors, was reported to bind and suppress NF-kB activation (Heppner et al, 2001). Regarding the tumor suppressor p53, it was reported that p53 generally inhibits NF-kB function, and vice versa (Webster and Perkins, 1999); however, more complex relationships between p53 and NF-kB have emerged (see below).…”
Section: Inhibition Of Nf-jb By Tumor Suppressorsmentioning
confidence: 99%
“…Menin has been shown specifically interacts with JunD but not with other members of Jun family (c-Jun, JunB), as their interactions are mediated through the far N-terminal region of JunD that is missing in c-Jun and JunB (Aggarwal et al, 1999). In addition to JunD, Menin is also known to interact with other transcription factors, including NF-κB, Smad3, and Pem, implicating a general role of Menin in regulating transcription (Heppner et al, 2001;Kaji et al, 2001;Lemmens et al, 2001). Menin is known to repress JunD-activated transcription.…”
Section: Menin Represses Jund Transcriptional Activity In Protein Kinmentioning
confidence: 99%
“…Furthermore, Menin inactivation by antisense RNA antagonizes cell growth inhibition mediated by TGF-b (Kaji et al, 2001). Conversely, Menin interacts with the AP-1 transcription factor JunD and with NF-kB proteins and represses both NF-kB-mediated and JunD-dependent transcription Gobl et al, 1999;Heppner et al, 2001).…”
Section: Introductionmentioning
confidence: 99%